"Choose Physical Therapy" for Neonatal Abstinence Syndrome: Clinical Management for Infants Affected by the Opioid Crisis. Issue 6 (3rd June 2019) - McCarty, Dana B; Peat, Jennifer R; O'Donnell, Shannon; Graham, Elisabeth; Malcolm, William F
Abstract: In response to the opioid crisis, the American Physical Therapy Association has strongly advocated for physical therapy as a safe alternative to pharmacological pain management through the "#ChoosePT" campaign and the dedication of a PTJ special issue to the nonpharmacological management of pain. Physical therapists not only play an important role in the rehabilitation of the nearly 2 million adolescents and adults addicted to prescription opioids but also provide care to infants born to mothers with various drug addictions. This Perspective article explores the incidence, pathophysiology, and risk factors for neonatal abstinence syndrome and describes the clinical presentations of withdrawal and neurotoxicity in infants. Discipline-specific recommendations for the physical therapist examination and plan of care, including pharmacological management considerations, are outlined. Nonpharmacological management, including supportive care, feeding, parent education, social aspects of care, and follow-up services, are discussed from a physical therapy perspective. Finally, this article reviews developmental outcomes in infants with neonatal abstinence syndrome and reflects on challenges and future directions of research in this area.